The Local Stability of Solutions for a Nonlinear Equation - Haibo Yan; Ls Yong (Abstract and Applied Analysis)
The approach of Kruzkov’s device of doubling the variables is applied to establish the local stability of strong solutions for a nonlinear partial differential equation in the space L1(R) by assuming that the initial value only lies in the space L1(R)∩L∞(R).